2023
DOI: 10.3389/fcell.2022.1015665
|View full text |Cite
|
Sign up to set email alerts
|

RSK1 and RSK2 serine/threonine kinases regulate different transcription programs in cancer

Abstract: The 90 kDa ribosomal S6 kinases (RSKs) are serine threonine kinases comprising four isoforms. The isoforms can have overlapping functions in regulation of migration, invasion, proliferation, survival, and transcription in various cancer types. However, isoform specific differences in RSK1 versus RSK2 functions in gene regulation are not yet defined. Here, we delineate ribosomal S6 kinases isoform-specific transcriptional gene regulation by comparing transcription programs in RSK1 and RSK2 knockout cells using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…Ramos showed that even in the same cell-type, two RSKs regulate different transcription programs. By using microarray analysis in glioblastoma-derived cells were RSK1 or RSK2 were knocked-down, this group showed that these two kinases do not induce the same gene transcription patterns ( 20 ). In brief, RSKs and their link to cancer clearly depends on the RSK isoform and the type of cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ramos showed that even in the same cell-type, two RSKs regulate different transcription programs. By using microarray analysis in glioblastoma-derived cells were RSK1 or RSK2 were knocked-down, this group showed that these two kinases do not induce the same gene transcription patterns ( 20 ). In brief, RSKs and their link to cancer clearly depends on the RSK isoform and the type of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In line with these data, a recent study showed that all four RSK isoforms were phosphorylating very similar peptides in a peptide array type of screening ( 12 ). Other works however support nonredundant activities of the distinct RSK isoforms in cells, likely linked to differences in the range of substrates phosphorylated by the different kinase isoforms ( 20 ).…”
mentioning
confidence: 99%
“…Both of these inhibitors have shown efficacy in xenograft models. In cancer RSK1 and RSK2 regulate differing transcriptional programs in glioblastoma multiforme ( Yang et al, 2022 ). Additionally, in lung cancer RSK1 appears to function as a tumor suppressor whereas RSK2 promoted metastasis ( Lara et al, 2011 ).…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…This clinical phatology involves several risks factors such age (Zabransky et al, 2022), smoking (Phua et al, 2022), alcohol consumption (Mayen et al, 2022), obesity (Bao et al, 2022), diabetes (Lazarus and Bays, 2022), physical inactivity (Minihan et al, 2022), radiation exposure (Einstein et al, 2007), and genetic factors (Garcia-Pelaez et al, 2022;Jiang et al, 2023). In this way, several genetic expressions have been involved in the development of cancers; for example, the expression of ribosomal S6 p90 kinase family [RSK 1-4; which belongs to the group of highly conserved Ser/Thr kinases] (Yang et al, 2023;Casalvieri et al, 2017). In addition, a study showed that RSK-1 could be associated to tumor growth and metastasis, using a triple-negative breast cancer model (Czaplinska et al, 2018).…”
Section: Introductionmentioning
confidence: 99%